Make Room for Play: An Evaluation of a Campaign Promoting Active Play. Issue 1 (2nd January 2019) - Priebe, Carly S.; Latimer-Cheung, Amy E.; Berry, Tanya; O'Reilly, Norm; Rhodes, Ryan E.; Spence, John C.; Tremblay, Mark S.; Faulkner, Guy
Abstract : In the context of rising screen time, only a third of Canadian children are achieving adequate amounts of active play, an important source of physical activity. ParticipACTION, a national not-for-profit organization, created the "Make Room for Play" campaign targeting parents with television advertisements depicting how screen time takes away from active play. The advertisements featured children engaging in active play (e.g., jump rope) while a black screen progressively sequesters the room for them to play. This study's purpose was to evaluate the campaign using the hierarchy of effects model, a framework for conceptualizing the impact of mass media campaigns. It was hypothesized that recall would relate to intermediate (e.g., cognitions, self-efficacy) and distal (e.g., parental support) factors. Twenty-six percent of the general population and caregiver samples surveyed ( N = 1576) recalled (unaided) the advertisement and 45.9% recalled when prompted. Parental support was significantly higher in those recalling the campaign, p = .009. Twenty-four percent of parents reporting unaided recall (versus 14.0% of those not) tried to engage in active play with their children and 21.2% (versus 12.0%) tried to create opportunities for children to engage in play. Strengths and limitations of mass media approaches targeting active play and screen time are discussed.